Modulation of mammary cancer cell migration by 15-deoxy-Δ(12,14)-prostaglandin J(2): implications for anti-metastatic therapy - Diers, Anne R. (2010)
Recently, a number of steps in the progression of metastatic disease have been shown to be regulated by redox signaling. Electrophilic lipids affect redox signaling through the post-translational modification of critical cysteine residues in proteins. However, the therapeutic potential as well as the precise mechanisms of action of electrophilic lipids in cancer cells is poorly understood. In this study, we investigate the effect of the electrophilic prostaglandin 15-deoxy-Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) on metastatic properties of breast cancer cells. 15d-PGJ(2) was shown to decrease migration, stimulate focal adhesion disassembly and cause extensive F-actin reorganization at low concentrations (0.03-0.3 μM). Importantly, these effects seem to be independent of PPARγ and modification of actin or Keap1, which are known protein targets of 15d-PGJ(2) at higher concentrations. Interestingly, the p38 inhibitor SB203580 was able to prevent both 15d-PGJ(2)-induced F-actin reorganization and focal adhesion disassembly. Taken together, our results suggest that electrophiles such as 15d-PGJ(2) are potential anti-metastatic agents which exhibit specificity for migration and adhesion pathways at low concentrations where there are no observed effects on Keap1 or cytotoxicity.